Pathologic diagnosis of malignant mesothelioma: chronological prospect and advent of recommendations and guidelines - Valeria Ascoli (Istituto Superiore di Sanità, 2015)
Malignant mesothelioma (MM) is rare and difficult to diagnose. Its identification depends upon pathological investigation (cyto-histological assessment and immunohistochemistry) supported by clinical and radiological evidence. In the last decade, the standardization of diagnostic methods has become a major focus of debate among pathologists and clinicians. This has led to the writing of guidelines and recommendation for the diagnosis to achieve the goal of a standard diagnosis. In this article, a chronological view relating to the pathological diagnosis of MM is presented together with a review of guidelines and recommendations.